Towards Inclusive Syllabi in University and College Classrooms - Costa, Christina Naegeli; Stewart, Nathaniel D. (Journal of Teaching and Learning, 2026)
Syllabi are foundational documents for higher education pedagogies because they shape the learning experience for professors and students. This work explores key aspects of crafting an inclusive syllabus that promotes belonging, accessible design, asset-based content, inclusive language, and communicating dedication to accessible education through an inclusivity statement. Inclusivity isn't just ethical; it's essential. Accessible design ensures students have access to course materials; asset-based content broadens perspectives, promotes critical thinking, and affirms the experiences of students experiencing systemic marginalization; inclusive language fosters a welcoming atmosphere; and the inclusivity statement underscores the educator’s commitment to accessible education. Crafting an inclusive syllabus is complex, potentially transformative, and empowering for educators as champions of diversity, and contributes to greater equity in higher education within the realm of psychology. The strategies outlined are intended for immediate application by higher education faculty and staff seeking to transform their teaching environments.